2008
DOI: 10.1075/pbns.169
|View full text |Cite
|
Sign up to set email alerts
|

Contrastive Rhetoric

Abstract: This volume explores contrastive rhetoric for audiences in both ESL contexts and international EFL contexts, exposing the newest developments in theories of culture and discourse and pushing the boundaries beyond any previously staked ground. The book presents a comprehensive set of empirical investigations involving a number of first languages; 13 of the 17 authors are English-as-a-second-language speakers, many working in non-US contexts. This work develops a coherent agenda for contrastive rhetoric research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Contrastive Rhetoric (CR) is another approach to academic writing. It is based on relativistic assumptions that different cultures have different conventions for texts and literacy practices (Connor, 1996;Connor, Nagelhout, & Rozycki, 2008). The "father" of contrastive rhetoric, Kaplan (1966), studied texts written by learners with English as a second language and with different first languages.…”
Section: Contrastive Rhetoricmentioning
confidence: 99%
“…Contrastive Rhetoric (CR) is another approach to academic writing. It is based on relativistic assumptions that different cultures have different conventions for texts and literacy practices (Connor, 1996;Connor, Nagelhout, & Rozycki, 2008). The "father" of contrastive rhetoric, Kaplan (1966), studied texts written by learners with English as a second language and with different first languages.…”
Section: Contrastive Rhetoricmentioning
confidence: 99%
“…SLA researchers who investigated L1 influence looked at how the language learner used his/her knowledge of the linguistic properties of the L1 to perform various phonological, morphological, syntactic, and lexical functions in the L2 (e.g., Pasquarella, Chen, Lam, Luo, & Ramirez, 2011). Moving beyond the sentence level, L1 influence research targeted the L1-based discourse patterns of learner language in order to show how they utilized the L1-based cohesive devices to link sentences in the L2 (Connor et al, 2008). In order to investigate L1 influence, SLA researchers collected interactional data and concentrated on identifying the discourse patterns produced by the L2 learners that were deviant from native speaker norms.…”
Section: L1 Influence In Sla Studiesmentioning
confidence: 99%
“…The data analysis revealed that the Chinese speakers not only used cohesive devices for the purpose of connecting sentences, but in some cases for adding new ideas to their interactions with the native speakers. This added function was different from the English norm of restricting the use of cohesive devices for the purpose of connecting sentences (Connor et al, 2008). For example, when a Chinese speaker introduces a new point, he/she may use the cohesive devices of "conjunction" or "disjunction" not only to connect utterances, but also to introduce new ideas that support the main point.…”
Section: L1 Influence On the Use Of Cohesive Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Is this due to first language (L1) interference and/or a lack of instruction and thus a lack of awareness of what is required (McCune, 2004). While early research has indicated that L1 rhetorical patterns and linguistic devices negatively interfere with second language (L2) writing (e.g., the seminal work of Kaplan, 1966); research has shown that with certain specific instructional methods towards disciplinary writing students showed ability to develop their L2 writing in their discipline communities (Connor, Nagelhout, & Rozycki, 2008;Feez, 1998;Ferris & Hedgcock, 2004;Hyland, 2017;Johns, 2001;Mukattash, 2003;Swales, 1990 among others). Thus, this study aims to investigate possible cause(s) of any writing problems that L1 Arabic students have in writing academic essays, one required genre at the university level.…”
Section: Statement Of the Problemmentioning
confidence: 99%